Continuous functions satisfying a given condition

Calculus Level 5

The number of continuous functions f : R R f:\mathbb{R} \longrightarrow \mathbb{R} such that ( f ( x ) ) 2 + x 4 = x ( 1 + x 2 ) f ( x ) (f(x))^{2}+x^{4}=x(1+x^{2}) f(x) for all real numbers x x are?


The answer is 16.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

By completing the square, for all real numbers x x , we have

( f ( x ) ) 2 + x 4 = x ( 1 + x 2 ) f ( x ) ( f ( x ) ) 2 2 x 2 ( 1 + x 2 ) f ( x ) + [ x 2 ( 1 + x 2 ) ] 2 = [ x 2 ( 1 + x 2 ) ] 2 x 4 [ f ( x ) x 2 ( 1 + x 2 ) ] 2 = [ x ( x 2 1 ) 2 ] 2 ( 1 ) \begin{aligned} & {{\left( f\left( x \right) \right)}^{2}}+{{x}^{4}}=x\left( 1+{{x}^{2}} \right)f\left( x \right) \\ & \Leftrightarrow {{\left( f\left( x \right) \right)}^{2}}-2\frac{x}{2}\left( 1+{{x}^{2}} \right)f\left( x \right)+{{\left[ \frac{x}{2}\left( 1+{{x}^{2}} \right) \right]}^{2}}={{\left[ \frac{x}{2}\left( 1+{{x}^{2}} \right) \right]}^{2}}-{{x}^{4}} \\ & \Leftrightarrow {{\left[ f\left( x \right)-\frac{x}{2}\left( 1+{{x}^{2}} \right) \right]}^{2}}={{\left[ \frac{x\left( {{x}^{2}}-1 \right)}{2} \right]}^{2}} \ \ \ \ \ (1) \\ \end{aligned} Let g ( x ) = f ( x ) x 2 ( 1 + x 2 ) g\left( x \right)=f\left( x \right)-\dfrac{x}{2}\left( 1+{{x}^{2}} \right) , x R x\in \mathbb{R} . Then, g ( x ) = 0 ( 1 ) x ( x 2 1 ) 2 = 0 x = 0 g\left( x \right)=0\overset{(1)}{\mathop{\Leftrightarrow }}\,\dfrac{x\left( {{x}^{2}}-1 \right)}{2}=0\Leftrightarrow x=0 , or x = ± 1 x=\pm 1 . Since g g is continuous, in the intervals defined by any two consecutive zeros, g ( x ) g(x) maintains a positive or a negative sign and is equal either to x ( x 2 1 ) 2 \dfrac{x\left( {{x}^{2}}-1 \right)}{2} , or x ( x 2 1 ) 2 -\dfrac{x\left( {{x}^{2}}-1 \right)}{2} .

Consequently, in every interval, either f ( x ) = g ( x ) + x 2 ( 1 + x 2 ) = x ( x 2 1 ) 2 + x 2 ( 1 + x 2 ) = x 3 , f\left( x \right)=g\left( x \right)+\frac{x}{2}\left( 1+{{x}^{2}} \right)=\frac{x\left( {{x}^{2}}-1 \right)}{2}+\frac{x}{2}\left( 1+{{x}^{2}} \right)={{x}^{3}}, or f ( x ) = g ( x ) + x 2 ( 1 + x 2 ) = x ( x 2 1 ) 2 + x 2 ( 1 + x 2 ) = x . f\left( x \right)=g\left( x \right)+\frac{x}{2}\left( 1+{{x}^{2}} \right)=-\frac{x\left( {{x}^{2}}-1 \right)}{2}+\frac{x}{2}\left( 1+{{x}^{2}} \right)=x. For the four intervals ( , 1 ) \left( -\infty ,\ -1 \right) , ( 1 , 0 ) \left( -1 ,\ 0 \right) , ( 0 , 1 ) \left( 0 ,\ 1 \right) , ( 1 , + ) \left( 1 ,\ + \infty \right) , there are 2 4 = 16 {{2}^{4}}=16 different combinations. Hence, the number of different continuous functions f f that satisfy the given equation is 16 \boxed{16} .

Pegajoso Piston
Oct 23, 2020

Rewrite the equation. ( f ( x ) ) 2 + x 4 = x ( 1 + x 2 ) f ( x ) ( f ( x ) ) 2 x ( x 2 + 1 ) ( f ( x ) ) + x 4 = 0 \\ \left(f\left(x\right)\right)^2+x^4 = x\left(1+x^2\right)f\left(x\right) \\ \left(f\left(x\right)\right)^2-x\left(x^2+1\right)\left(f\left(x\right)\right)+x^4 = 0 \\ Use the quadratic equation to isolate f ( x ) f\left(x\right) f ( x ) = x ( x 2 + 1 ) ± ( x ( x 2 + 1 ) ) 2 4 x 4 2 \\ f\left(x\right) = \frac{x\left(x^2+1\right) \pm \sqrt{\left(x\left(x^2+1\right)\right)^2-4x^4}}{2} \\ We cannot just take two solutions as plus and with minus. The plus-minus symbol can be either positive or negative at any point. To see what to do to stay continuous, we must transform the equation further. f ( x ) = x ( x 2 + 1 ) ± x 2 ( x 2 + 1 ) 2 4 x 4 2 f ( x ) = x ( x 2 + 1 ) ± x 2 ( ( x 2 + 1 ) 2 4 x 2 ) 2 f ( x ) = x ( x 2 + 1 ) ± x 2 ( ( x 4 + 2 x 2 + 1 ) 4 x 2 ) 2 f ( x ) = x ( x 2 + 1 ) ± x 2 ( x 4 2 x 2 + 1 ) 2 f ( x ) = x ( x 2 + 1 ) ± x 2 ( x 2 1 ) 2 2 f ( x ) = x ( x 2 + 1 ) ± ( x ( x 2 1 ) ) 2 f ( x ) = x ( x 2 + 1 ) ± ( x 1 ) ( x ) ( x + 1 ) 2 \\ f\left(x\right) = \frac{x\left(x^2+1\right) \pm \sqrt{x^2\left(x^2+1\right)^2-4x^4}}{2} \\ f\left(x\right) = \frac{x\left(x^2+1\right) \pm \sqrt{x^2\left(\left(x^2+1\right)^2-4x^2\right)}}{2} \\ f\left(x\right) = \frac{x\left(x^2+1\right) \pm \sqrt{x^2\left(\left(x^4+2x^2+1\right)-4x^2\right)}}{2} \\ f\left(x\right) = \frac{x\left(x^2+1\right) \pm \sqrt{x^2\left(x^4-2x^2+1\right)}}{2} \\ f\left(x\right) = \frac{x\left(x^2+1\right) \pm \sqrt{x^2\left(x^2-1\right)^2}}{2} \\ f\left(x\right) = \frac{x\left(x^2+1\right) \pm \left(x\left(x^2-1\right)\right)}{2} \\ f\left(x\right) = \frac{x\left(x^2+1\right) \pm \left(x-1\right)\left(x\right)\left(x+1\right)}{2} \\ The plus-minus term is zero at and only at x equaling negative one, zero, or positive one. This gives us four regions: x < 1 , 1 < x < 0 , 0 < x < 1 , 1 < x x<-1,-1<x<0,0<x<1,1<x . To stay continuous, whether the plus-minus sign "acts" as a positive or negative sign must be the same within the region, as within the region the plus-minus term is never zero. The four regions, however, may have different signs from each other.

Each of these four values has a binary choice, either plus or minus. This gives us a total number of possibilities of 2 4 = 16 2^4=16\\ Perhaps this can be seen more clearly with a graph: We can clearly see that to keep the graph a function and continuous, there must be a choice in 4 regions of taking the "top-half" or "bottom-half" of the region. Apologies if this doesn't make much sense, this is just how it makes the most sense to me.

Actually I think it is neater to say f(x)=x or x^3

Isaac YIU Math Studio - 7 months, 3 weeks ago
Patrick Corn
Oct 27, 2020

Let y = f ( x ) . y=f(x). Then the equation factors: ( y x ) ( y x 3 ) = 0. (y-x)(y-x^3) = 0. When x = 1 , 0 , 1 , x = -1,0,1, we get y = 1 , 0 , 1 y = -1,0,1 respectively. These are the only intersection points of y = x y=x and y = x 3 . y=x^3. So the general form is f ( x ) = { f 1 ( x ) x 1 f 2 ( x ) 1 x 0 f 3 ( x ) 0 x 1 f 4 ( x ) 1 x f(x) = \begin{cases} f_1(x) & x \le -1 \\ f_2(x) & -1 \le x \le 0 \\ f_3(x) & 0 \le x \le 1 \\ f_4(x) & 1 \le x \end{cases} where f i ( x ) = x f_i(x) = x or f i ( x ) = x 3 f_i(x) = x^3 for all i . i. Since there are two choices for each i , i, there are 2 4 = 16 2^4 = 16 choices for f . f.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...